2016
DOI: 10.3126/nepjoph.v8i1.16158
|View full text |Cite
|
Sign up to set email alerts
|

Eye changes among HIV positive patients on antiretroviral therapy in Nepal

Abstract: Background: HIV/AIDS has various ocular manifestations. Objective: To find out eye findings among HIV positive patients in the era of antiretroviral therapy. Method This Hospital based cross sectional descriptive study was carried at B. P. Koirala Lions Centre for Ophthalmic Studies. Patient profile, WHO clinical stage, CD4+ cell count, duration of HIV, antiretroviral therapy, and systemic diseases were recorded. All the cases underwent ocular examination as per the study protocol and the findings were noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Studies from sub-Saharan Africa reported that 48% of PLHIV in Ghana [4] and 70% of PLHIV in Tanzania [5] had ocular abnormalities. Elsewhere, ocular conditions have been reported in 53 to 65% of PLHIV at some point in their disease course [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from sub-Saharan Africa reported that 48% of PLHIV in Ghana [4] and 70% of PLHIV in Tanzania [5] had ocular abnormalities. Elsewhere, ocular conditions have been reported in 53 to 65% of PLHIV at some point in their disease course [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Within these bodily fluids, HIV is present as both free virus particles and virus within infected immune cells. 3 The virus infect T lymphocytes resulting in profound immunodeficiency leading to opportunistic infections and neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…HIV is transmitted by blood, semen, vaginal fluid, pre-ejaculate or breast milk. Within these bodily fluids, HIV is present as both free virus particles and virus within infected immune cells [3]. The virus infect T lymphocytes resulting in profound immunodeficiency leading to opportunistic infections and neoplasms.…”
Section: Introductionmentioning
confidence: 99%